Mineralization of malathion by Fusarium oxysporum strain JASA1 isolated from sugarcane fields. Issue 1 (28th March 2014) - Peter, Logeswari; Gajendiran, Anudurga; Mani, Deepa; Nagaraj, Sugitha; Abraham, Jayanthi
<x xml:space="preserve">Abstract</x> The present work was focused in isolating fungus which possessed the special ability to degrade malathion. The pesticide of choice was malathion as it is being used to control a variety of pests in the agricultural fields in India. The fungal strains with the potential to degrade malathion was isolated by enrichment technique from malathion contaminated soil. The molecular characterization of 18S rRNA sequence homology confirmed its identity as Fusarium oxysporum. The isolate was able to degrade 400 mg L−1 malathion completely in mineral medium. In soil spiked with malathion and with addition of nutrients (carbon, nitrogen, phosphate), the isolate was capable of degrading malathion at 8th day of incubation. Where as in the second trial, in the absence of nutrients, JASA1 was able to degrade 400 mg L−1 malathion on the 9th day of incubation. The course of the degradation process was studied using High performance liquid chromatography (HPLC) and Fourier transform infrared (FTIR) analyses which confirmed the degradation potential of the fungus. © 2014 American Institute of Chemical Engineers Environ Prog, 34: 112–116, 2015